Dynamic compressive mechanical properties of fibre-reinforced geopolymer concrete - Jihao Su; Jize Mao; Bukui Zhou; Wei Zhang; Limei Wang; Chaomin Mu (Case Studies in Construction Materials)
To investigate the influence of different fibre types on the dynamic mechanical properties of geopolymer concrete (GPC), this study conducted experimental research on fibre-reinforced geopolymer concrete (FRGC) incorporating either steel or basalt fibres. Dynamic compression tests were performed using a 50 mm diameter split Hopkinson pressure bar (SHPB) at varying strain rates ranging from 69.1 to 235 s⁻¹ . The failure process of the specimens during impact was recorded using high-speed camera technology. The research analyzed the effects of fibre types on static compressive strength, dynamic failure processes, damage modes, dynamic compressive strength, specific energy absorption, and the dynamic increase factor (DIF). The results indicated that steel fibres have the better performance in enhancing static compressive strength, which can achieve a 23.2 % increase compared to plain high-strength geopolymer concrete (PGPC). A positive correlation was found between compressive strength and strain rate for all GPC and FRGC specimens. Under the tested strain rates, specimens containing basalt fibres demonstrated greater strain rate sensitivity in compressive strength compared to those containing steel fibres. Additionally, corresponding empirical formulas were proposed to predict the DIF and specific energy absorption for both GPC and FRGC.